Pelatihan Sistem Informasi Pelayanan Surat Pengantar Untuk Perangkat Desa Mangunjaya Kecamatan Tambun Selatan Kabupaten Bekasi - Mayadi, Mayadi; Kustanto, Prio (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Utilization of information and communication technology is applied to help facilitate human work and make it easier to get information. Utilization of information technology for government agencies is a useful tool to improve services to the community. Mangunjaya Village is a government agency at the village level that directly provides services to the community. The services provided include making cover letters, such as Identity Cards (KTP), Family Cards (KK) and Birth Certificates. With the help of information system technology, the Cover Letter service for the Mangunjaya Village Apparatus, Tambun Selatan District, is expected to help the community service so that it can be relatively more optimal and faster. This activity, which was held in Mangunjaya Village, out of a total of 30 participants who expressed satisfaction with the seminar held in Mangunjaya Village, as many as 57% were very satisfied, 30% satisfied and 13% said they were quite satisfied with the presentation delivered by the speaker.